Evidence for the Interactions Occurring Between Ionic Liquids and Tetraethylene Glycol in Binary Mixtures and Aqueous Biphasic Systems - Tome, Luciana I. N.
The well-recognized advantageous properties of poly(ethylene glycol)s (PEGs) and ionic liquids (ILs) in the context of an increasing demand for safe and efficient biotechnological processes has led to a growing interest in the study of their combinations for a wide range of procedures within the framework of green chemistry. Recently, one of the most promising and attractive applications has been the novel IL/polymer-based aqueous biphasic systems (ABS) for the extraction and purification of biomolecules. There still lacks, however, a comprehensive picture of the molecular phenomena that control the phase behavior of these systems. In order to further delve into the interactions that govern the mutual solubilities between ILs and PEGs and the formation of PEG/IL-based ABS, H-1 NMR spectroscopy in combination with classical molecular dynamics (MD) simulations performed for binary mixtures of tetraethylene glycol (TEG) and 1-alkyl-3-methylimidazolium-chloride-based ILs and for the corresponding ternary TEG/IL/water solutions, at T = 298.15 K, were employed in this work. The results of the simulations show that the mutual solubilities of the ILs and TEG are mainly governed by the hydrogen bonds established between the chloride anion and the -OH group of the polymer in the binary systems. Additionally, the formation of IL/PEG-based ABS is shown to be controlled by a competition between water and chloride for the interactions with the hydroxyl group of TEG.